Geriatric Sinus Surgery: A Review of Demographic Variables, Surgical Success and Complications in Elderly Surgical Patients. (June 2021) - Helman, Samuel N.; Carlton, Daniel; Deutsch, Brian; Choake, Robert; Patel, Varun; Govindaraj, Satish; Iloreta, Alfred M. C.; Del Signore, Anthony
Objective: Demonstrate feasibility, safety and outcome metrics of geriatric sinus surgery (GESS). Study Design: Retrospective review of patients undergoing sinus surgery for indication of chronic rhinosinusitis with and without nasal polyposis. Setting: Tertiary referral center. Participants: Patients who underwent FESS from 2008–2017; excluding skull base, craniofacial, or oncologic surgery. Primary study group were patients aged 65 years and older. Patients aged 40–64 years of age were included for comparison. Main Outcomes and Measures: Multivariate analysis was performed to identify independently associated patient characteristics and perioperative variables. Preoperative medical and treatment history, revision and primary surgery, preoperative and post-operative SNOT-22 and NOSE scores, Lund-McKay scores were recorded when available. Post-operative data was assessed at a minimum of two months after the index procedure. Post-operative complications were included. Results: Ninety-one (91) patients met criteria. 21.2% of the geriatric patients were taking systemic anticoagulation prior to surgery, and underwent treatment with nasal steroids (25.0%), oral antibiotics (67.7%), nasal irrigations (48.4%), and systemic steroids (37.5%) over an average of 7.3 months prior to surgery. There was an average post-operative reduction of 15.0 points (p < 0.0001) and 42.5 points (p = 0.0008) for SNOT-22 and NOSE scores, respectively. Average operative time was 117.4 minutes in geriatric patients compared to 183.4 minutes in younger patients (p = 0.004), with an average estimated blood loss of 55.6 milliliters (mL) compared to younger patients (111.8 mL) (p = 0.04). Linear regression identified revision surgery as associated with reductions in Sinonasal Outcome Test (SNOT-22) scores (p = 0.011). Geriatric patients had a shorter operative time (p = 0.011) while male sex was associated with a longer operative time (p = 0.014). Patients over 65 had fewer minor complications (p = 0.01), and there were no major complications in either group. Conclusions and Relevance: Geriatric sinus surgery is effective and safe in this cohort of patients.